First Multi-Organ Full-Length Transcriptome of Tree Fern Alsophila spinulosa Highlights the Stress-Resistant and Light-Adapted Genes - Hong, Yongfeng; Wang, Zhen; Li, Minghui; Su, Yingjuan; Wang, Ting (Frontiers in Genetics, 2022)
Alsophila spinulosa, a relict tree fern, is a valuable plant for investigating environmental adaptations. Its genetic resources, however, are scarce. We used the PacBio and Illumina platforms to sequence the polyadenylated RNA of A. spinulosa root, rachis, and pinna, yielding 125,758, 89,107, and 89,332 unigenes, respectively. Combining the unigenes from three organs yielded a non-redundant reference transcriptome with 278,357 unigenes and N50 of 4141 bp, which were further reconstructed into 38,470 UniTransModels. According to functional annotation, pentatricopeptide repeat genes and retrotransposon-encoded polyprotein genes are the most abundant unigenes. Clean reads mapping to the full-length transcriptome are used to assess the expression of unigenes. The stress-induced ASR genes are highly expressed in all three organs, which is validated by qRT-PCR. The organ-specific up-regulated genes are enriched for pathways involved in stress response, secondary metabolites, and photosynthesis. Genes for five types of photoreceptors, CRY signaling pathway, ABA biosynthesis and transduction pathway, and stomatal movement-related ion channel/transporter are profiled using the high-quality unigenes. The gene expression pattern coincides with the previously identified stomatal characteristics of fern. This study is the first multi-organ full-length transcriptome report of a tree fern species. The abundant genetic resources and comprehensive analysis of A. spinulosa, which provide the groundwork for future tree fern research.